(untitled) (Herald of Journalism, 2018)
The article considers features of the formation of varants of case endings in the Kazakh language. In spite of the fact that the case endings can be used interchangeably one can link thir functions with the same degree of grammatical meaning in the sentence. As a result, syntactic variants are formed that lead to conjugation of frequently appearing case endings in modern Kazakh language. The peculiarities of using the variant and changes in case endings as well as their omission and the formation of syntactic variants based on the opinions of the researchers in the Kazakh language from the point of view of scientific norms are considered. This phenomenon manifests itself in the case of case endings although grammatical function of these combinations is the same, but there is a semantic difference on the other hand, a dynamic state is manifested, an on the other, the static state and its significance are viewed from all sides. Case endings are used alone instead of others and examples of word formation options are considered using this method. Also, authors argue that this phenomenon is often found in works of art in Kazakh language.